The Effect of e-WOM, Perceived Value, Trust on Online Consumer Behavioral Intention: Perspective of Consumer from Pakistan - Ahmad, Naveed; Harun, Amran; Kamal Rashid, Nian; Othman, Bestoon; Muhammad Usman Khizer, Hafiz; Khan, Shumaila (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to measure the impact of e-WOM, trust, and perceived value on consumer behavioral intention. The sampling technique that was used in this research is a convenience sampling technique. Data were collected using a questionnaire involving 233 participants from Bahawalpur, Pakistan. Those participants who had online shopping experience were then analyzed using a statistical test by SmartPLS. The result of this study indicated a significant and positive impact of e-WOM, trust, and the perceived value on consumer behavioral intention. Limited studies have been carried out to address the consumer behavior of Bahawalpur in the Pakistani context. Further, this study discussed recommendations for practitioners and future studies.